The Use of Information Communication and Technology (ICT) to Enable Transparency, Accountability, and Participation in Indonesia - Asmiar Reza Agustina; Tutik Rachmawati (Indonesian Association for Public Administration (IAPA), 2020)
This research aims at understanding how ICT as panopticon vision enable transparency, accountability, and Participation in Indonesia. The betterment of these three aspects is believed to be beneficial for the government in fighting corruption. In the transparency aspect, this research has eight indicators which are constructed from studies by Bhatmagar, Davies & Fumega, Park & Florida, Grimmelikhuijsen, Keuffer & Mabillard: (1) the availability of laws and regulations, (2) the availability of government budget allocations and spending, (3) the availability of performance reports, (4) open government processes, (5) identification of elected officials and civil servants under investigation for corruption and fraudulent activities, (6) disclosure of assets and investments of public officials, (7) provision of e-procurement, and (8) using file formats. In the accountability aspect, four indicators from studies of Lee & Kwak and Davies & Fumega are used. They are (1) the availability of social media presence, (2) using mainstream social media for interactive, on-going conversations, storytelling, and communications, (3) the availability of a platform for questions and answers, and (4) the availability of information about feedback from the public. Finally, for the aspect of Participation, three indicators by Lee & Kwak are employed. Those are (1) voting and polling for a decision-making process or a public organization assessment, (2) feedback and ideation platform, and (3) crowdsourcing to report corruption or grievances. This research uses a qualitative research approach. It is benefiting from the use of secondary data as a form of the big data source. Hence, this research is an initial attempt to exploit the availability of big data as a valid data source. To ensure the secondary data sources’ validity, the researchers employed a triangulation process of backgrounds and reference checking. The data analysis in this research is based on 2 ICT based initiatives; Government websites and apps. It is evident from this research finding that, first, there are 35 ICT based initiatives, 31 websites, and four apps. From these numbers, there are only18 websites and four apps that are available. Second, in general, those websites and apps do enable transparency, accountability, and Participation. Another important highlight of the finding is that three unidentified websites and ten websites are unsuccessful in promoting those three aspects. However, most of the websites and apps had turned out a success. In the meanwhile, ICT as panopticon vision also results in new corruption opportunities. This study highlights three examples of new corruption opportunities. It is recommended that Indonesia continue to work on those ten unavailable websites and, more importantly, be cautious and aware of the new corruption modes. Only by doing those, the role of ICT to fight corruption can be more strengthened.